Enhancing the Students’ Writing Skill through Technological Writing Feature of Wridea - Marleni Marleni (Journal of English Education and Teaching, 2020)
This study experimental research investigated the effect of using Wridea on enhancing EFL writing performance in PGRI University. It shed a light on how Wridea could enhance the writing skill. Wridea helped many of the participants to be more metacognitively aware of their English writing process. The results of this study showed that Wridea could be utilized as a service for improving the writing skill outside of the classrooms.